2021
DOI: 10.1590/1678-4685-gmb-2020-0330
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal dietary counseling in the first year of life on DNA methylation in a cohort of children

Abstract: Epigenetic modifications established during prenatal and early life, including DNA methylation, have been suggested as potential mediators of the interaction between environmental exposures during the perinatal period and adult metabolic health adverse outcomes, especially cardiometabolic complications and overweight. The effect of a dietary intervention in the first year of life on global methylation levels in leukocyte samples from a cohort of children born between 2001 and 2002 in southern Brazil was examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…As a result, these factors may play a role in the rise in global DNA methylation. The findings of this study support the idea that nutritional interventions should be made early in life [ 749 ]. In another study, Anderson et al [ 750 ] found that maternal vitamin D supplementation affects the methylation of genes involved in developmental processes in mothers and breastfed babies.…”
Section: Breastfeeding and Epigeneticssupporting
confidence: 84%
See 1 more Smart Citation
“…As a result, these factors may play a role in the rise in global DNA methylation. The findings of this study support the idea that nutritional interventions should be made early in life [ 749 ]. In another study, Anderson et al [ 750 ] found that maternal vitamin D supplementation affects the methylation of genes involved in developmental processes in mothers and breastfed babies.…”
Section: Breastfeeding and Epigeneticssupporting
confidence: 84%
“…The impact of dietary intervention in the first year of life on global methylation levels in leukocyte samples from a group of infants born in southern Brazil between 2001 and 2002 was investigated [ 749 ]. Overall methylation assessments were performed on DNA samples from 237 4-year-old children using enzyme-linked immunosorbent assays.…”
Section: Breastfeeding and Epigeneticsmentioning
confidence: 99%